Microfinance as a catalyst for women's empowerment: A study of Sindhuli District, Nepal - Shrestha, Sajeeb Kumar; Mahat, Dipak; Neupane, Dasarath; Karki, Tej Bahadur; Dongol, Padam; Kattel, Anuja (Edelweiss Applied Science and Technology, 2025)
This study examines the impact of microfinance programs on women’s economic empowerment in the Sindhuli district. It focuses on how micro-saving, micro-credit, micro-insurance, and training services contribute to improving women's financial independence and decision-making abilities. A cross-sectional research design with a deductive approach was used. Data were collected from 385 women who use microfinance services in the Sindhuli district. Participants were selected through purposive sampling. The data were analyzed using SmartPLS software to assess the relationship between microfinance services and women's economic empowerment. The results show that micro-saving, micro-credit, micro-insurance, and training services all have a significant positive effect on women’s economic empowerment. Microcredit supports women in starting or expanding businesses and managing emergencies. Micro-saving and insurance services provide financial security, while training helps build knowledge and confidence. Microfinance programs play an important role in increasing women’s economic independence and strengthening their decision-making power, especially in rural areas like Sindhuli. Microfinance institutions are encouraged to provide balanced services. Along with credit and savings, they should strengthen micro-insurance and training programs to better support women in low-income communities and promote sustainable development.